A Study of the Relationship Between Job Involvement and Employee Job Performance / Huzaidah Muhammad Shahar and Nur Fatin Abdul Rahman - Muhammad Shahar, Huzaidah; Abdul Rahman, Nur Fatin (2010)
This paper examined the influence factor of job involvement towards employee job performance at Tenaga Nasional Berhad (TNB). The elements of job involvement that contribute to job performance are employee commitment, rewards, skill variety and motivation. The population size consists of 500 employees from all the departments as a respondent, and the survey are collected by using Stratified Random Sampling. The objective of this research is to study the relationship between job involvement and employee job performance. This research also identifies the dominant job involvement elements influence employee job performance in the workplace.